Development of Ca2+, Cr3+ Co‐Doped and Pr3+, Ca2+, Cr3+ Tri‐Doped β‐Ga2O3 Persistent Luminescence Nanoparticles with Enhanced Luminescence. Issue 1 (7th January 2022) - Sun, Xue‐Feng; Abdurahman, Renagul; Chu, Gang‐Hui; Yang, Qian‐Ting; Yang, Tong‐Sheng
Abstract: The introduction of co‐dopants is one of the effective ways to improve the luminescence properties of the persistent luminescence nanoparticles (PLNPs). Herein, Cr 3+, Ca 2+ co‐doped and Cr 3+, Ca 2+, Pr 3+ tri‐doped β‐Ga2 O3 PLNPs with enhanced persistent luminescence were developed via the hydrothermal synthesis and subsequent calcinations, which improved the persistent luminescence of the β‐Ga2 O3 PLNPs. The results showed that the prepared PLNPs had a long afterglow time of more than 8 days with a signal‐to‐noise ratio (SNR) of 272 and the Quantum yield (QY) up to 74.8 %, which was renewable by LED lamps and stored information under a high‐temperature environment. The synthesized β‐Ga2 O3 :Cr 3+, Ca 2+, Pr 3+ PLNPs with long afterglow time showed great potentials in optical storage. Abstract : Cr 3+, Ca 2+ co‐doped and Cr 3+, Ca 2+, Pr 3+ tri‐doped β‐Ga2 O3 persistent luminescence nanoparticles (PLNPs) with enhanced persistent luminescence were developed via hydrothermal synthesis and subsequent calcinations, which improved the persistent luminescence of the β‐Ga2 O3 PLNPs. The results showed that the prepared PLNPs had a long afterglow time of more than 8 days, and showed great potentials in optical storage.